Ultrasound and electrophysiologic findings in patients with Guillain–Barré syndrome at disease onset and over a period of six months. Issue 2 (February 2016) - Grimm, Alexander; Décard, Bernhard F.; Schramm, Axel; Pröbstel, Anne-Katrin; Rasenack, Maria; Axer, Hubertus; Fuhr, Peter
Highlights: Enlarged cervical spinal and peripheral nerves detected by ultrasound might be an early marker for Guillain–Barré syndrome (GBS). Vagus enlargement occurs in patients with GBS, predominantly in those with autonomic dysregulation. Vagus nerve and spinal nerves normalize after six months, while the peripheral nerves remain enlarged. Abstract: Objective: To investigate cross-sectional areas (CSAs) of several peripheral nerves including the vagus nerve and the diameter of spinal nerves as measured by nerve ultrasound (NUS) and nerve conduction studies (NCS) in Guillain–Barré syndrome (GBS) patients over at least six months compared to healthy controls. Methods: NUS and/or NCS of several nerves, the vagus nerve, and the 5th/6th cervical spinal nerves were performed in patients with GBS at days 2–3 after symptom onset, at days 10–14 after immunoglobulin therapy and after six months compared to healthy controls. Results: 27 GBS-patients and 31 controls were included. Using NUS significant enlargement was found in all measured nerves ( P  < 0.001), except the sural nerve ( P  = 0.086) compared to the controls at onset. The vagus (median 3.0 mm 2 vs. 2.0 mm 2, P  < 0.0001) and the cervical spinal nerves were significantly enlarged (median 3.5/4.0 mm vs. 2.6/3.2 mm, p  < 0.0001), the vagus most obviously in patients with autonomic dysregulation (AD, 4.0 mm 2 ). Six months later, NCS showed persisting pathology in CMAP-amplitudes with amelioration of F-wave pathology. NUS showed restitution in the spinal nerves (median 2.6/3.2 mm) and the vagus (median 2.0 mm 2 ) in all patients excluding the vagus in those with persistent AD (median 4.0 mm 2 ). The peripheral nerves did not change significantly ( P  > 0.05). Conclusion: Ultrasonographic detection of cervical spinal nerve enlargement supports the diagnosis of GBS in the early phase. Its regression may be a good parameter for the clinical restitution over time. Vagus enlargement may be a risk marker for development of AD. Significance: Ultrasound is a reliable diagnostic follow-up tool in early GBS.